Evaluación posoperatoria de los pacientes con úlcera perforada - López Rodríguez, Pedro (2013)
SciELO Cuba. http://scielo.sld.cu/scielo.php?script=sci_arttext&pid=S0034-74932013000300003 http://scielo.sld.cu/pdf/cir/v52n3/cir03313.pdf